Evaluation of facilitative factors for preventing cognitive decline: A 3‐year cohort study of community intervention. Issue 1 (8th February 2016) - Kimura, Daisuke; Takeda, Tokunori; Ohura, Tomoko; Imai, Aiko
Abstract: Aim: We conducted a cohort study to elucidate paticipants' facilitative factors that may help to prevent cognitive decline. Methods: This study followed 100 participants (average age: 74.1 ± 5.8; 10 men, 90 women) for 3 years; participants had previously been part of the Taketoyo Project ( n = 366) in 2007–2011. The end‐point was defined as reduced cognitive function in elderly community residents participating in a preventive intervention for dementia. The presence or absence of reduced cognitive function at the end of the third year of intervention was the dependent variable, and all evaluation items were considered explanatory variables. After Fisher's exact test ( P < 0.15), stepwise multiple logistic regression analysis ( P < 0.05) was performed, and facilitative factors for prevention of cognitive decline were extracted. Results: Items with a significant adjusted odds ratio (OR) based on multiple logistic regression analysis were the three‐word delayed recall test (OR: 0.330, 95% confidence interval (CI): 0.142–0.767; P < 0.05), word fluency (OR: 0.565, 95%CI: 0.359–0.891; P < 0.05), frequency of going out (OR: 2.790, 95%CI: 0.803–6.380; P < 0.05) and number of friends with whom they engaged in activities (OR:0.344, 95%CI: 0.127–0.932; P < 0.05). Conclusion: Subjects who had maintained a certain level of cognitive function, engaged in activities with friends, and went out frequently at baseline were extracted. In other words, the results suggested that enhancement of social networks and leisure activities prompted by recreational centre participation had a positive effect on maintaining cognitive function. The results also suggest that to improve the effectiveness of preventive interventions for cognitive dysfunction, support for social factors and leisure activities, in addition to cognitive function, may improve the long‐term effectiveness of maintaining cognitive function.